Real-world safety evaluation of musculoskeletal adverse events associated with Korean pediatric fluoroquinolone use: a nationwide longitudinal retrospective cohort study - Kim, Yoonhye (Sci Rep, 2019)
Though the pediatric use of fluoroquinolones (FQs) is limited for musculoskeletal safety concerns, the clinical usefulness still exists. This study examined the association between FQs and musculoskeletal adverse events (AEs) as well as the possible risk factors associated with the pediatric FQs uses. This population-based, longitudinal, retrospective study was conducted using Korean National Sample Cohort database originating between 2002 and 2015. An FQ-treated pediatric cohort (<18 years old) was compared to a control treated with amoxicillin. Propensity score matching (PSM) and a Cox proportional hazard model was used to estimate the hazard ratio (HR) for a diagnosis of musculoskeletal AEs within 60 days of the first prescription. Among one million participants, total of 15,706 and 147,840 children were eligible for the FQ and amoxicillin cohorts, respectively. The PSM cohorts showed a slightly increased risk of musculoskeletal AEs after FQ treatment (HR, 1.19; 95% confidence interval, 1.01–1.40; p = 0.042). This association was stronger in males, older patients, and some FQs users. This study indicates that pediatric FQ use is associated with a risk of musculoskeletal AEs and that FQ use should be carefully monitored in groups with certain risk factors. Well-designed pragmatic trials could be expected to clarify these issues.